Hubungan Paritas, Pendidikan, dan Pekerjaan dengan Pemakaian Alat Kontrasepsi Suntik 3 Bulan di PMB Yusida Palembang Tahun 2021 - Fina Yanti; Eka Rahmawati; Titin Dewi Sartika Silaban (Universitas Batanghari Jambi, 2022)
Injectable contraception is the most-widely used contraception by fertile-aged women. The great number of 3-month injection of family planning acceptors is influenced by several factors, such as: age, education, occupation, income and parity. The objective of this study is to know whether there is a relationship of parity, education and occupation with the use of 3-month contraception. The research design used a cross sectional approach. The collected population consisted of all mothers who came to use Injectable contraception at PMB Yusida Am.Keb, Palembang City, totaling 261 respondents. From the Bivariate analysis, it was found that there was a non-significant relationship between parity and the use of 3-month contraception (p_value=0.750), a significant relationship between education and the use of 3-month contraception (p_value=0.036), and a non-significant relationship between occupation and the use of 3-month contraception (p_value=0.608). In conclusion, for the health workers, especially midwives who work at PMB Yusida Am.Keb, Palembang City in 2021, it is expected that this research result can be used as information about midwifery care, so that officers can provide maximum services in order to improve the quality of health services to the great number of 3-month injectable family planning contraception uses.